Optimalisasi Pengelolaan Bahan Baku Roti Dinar Dengan Implementasi Metode FIFO Untuk Meningkatkan Efisiensi Dan Kelancaran Operasional - Sulistyo, S; Srirahayu, Agustina; Sopingi, S (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to optimize the management of raw materials at the Dinar Bakery using the FIFO (First In, First Out) method to increase operational efficiency. Dinar Bakery faces problems in inventory management, such as unstructured storage and recording errors, due to limited human resources. Implementing FIFO is expected to reduce the risk of expiration, reduce storage costs and maximize the use of raw materials. The research results show that implementing FIFO can optimize inventory, reduce waste, and increase inventory rotation, so that stores can be more responsive to market demand and increase customer satisfaction. This research also provides a theoretical contribution to the literature on raw materials management in the food industry.